Preparation method of high-compaction lithium iron phosphate based on ferric phosphate with wide-range iron-phosphorus ratio

By adopting a high compaction method with a wide range of iron-phosphorus ratio in the preparation process of lithium iron phosphate, the problems of high raw material prices and narrow iron-phosphorus molar ratio in the prior art are solved, cost reduction and performance improvement are achieved, and are suitable for industrial production.

CN119797310APending Publication Date: 2025-04-11YUNNAN YUNTIANHUA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510019414.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the preparation process of lithium iron phosphate has high requirements for the iron-phosphorus molar ratio of iron phosphate raw materials, resulting in excessive raw material prices and increased production costs, and it is not suitable for iron phosphate raw materials with low phosphorus content and high iron content.

Method used

A high-pressure lithium iron phosphate preparation method based on a wide range of iron-phosphorus ratio is prepared by mixing carbon source, iron phosphate with a lithium source and adding a phosphorus supplement agent to prepare lithium iron phosphate products with an iron-phosphorus molar ratio range of 0.960 to 1.02:1.

Benefits of technology

It effectively widens the iron-phosphorus molar ratio range of iron phosphate raw materials, reduces production costs, and ensures that the various performances of lithium iron phosphate meet the requirements, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797310A_ABST
    Figure CN119797310A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium iron phosphate production, and discloses a high-compaction lithium iron phosphate preparation method based on iron phosphate with a wide-range iron-phosphorus ratio, which comprises the following steps: 1) mixing a carbon source, iron phosphate and a lithium source, adding a phosphorus supplement agent accounting for 0.2-1.2% of the mass of iron phosphate, and adding water to prepare slurry a; the molar ratio of iron to phosphorus in the iron phosphate is (0.960-1.02): 1; the molar ratio of the iron phosphate to the lithium source is 1: (1.00-1.05); the addition amount of the carbon source accounts for 5-10% of the total mass of the iron phosphate and the lithium source; and 2) stirring the slurry a, performing ball milling, performing spray drying, calcining, and performing air jet pulverization to obtain a lithium iron phosphate product with D50 of 0.8-2.0 [mu] m. The iron-phosphorus molar ratio range in the iron phosphate used in the method can reach 0.960-1.02: 1, the iron-phosphorus molar ratio range of the iron phosphate raw material is effectively widened, the price of the raw materials used for production is effectively reduced, and the method is simple in technological process and suitable for being used in industrial large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium iron phosphate production, and in particular to a method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios. Background Art

[0002] LiFePO4 is a new type of fine phosphorus chemical product and one of the most widely used positive electrode materials for lithium-ion batteries. It has the advantages of high energy density, low cost, stable charging and discharging platform, environmental friendliness and high safety.

[0003] At present, the main methods for synthesizing lithium iron phosphate are liquid phase method and solid phase method. The liquid phase method includes: solvothermal method, sol-gel method, coprecipitation method, emulsion drying method, etc. The liquid phase method is difficult, and only a few companies have achieved industrial production. The solid phase synthesis process is simple and mature, and it is the mainstream process in the industry, but the process has high requirements on the quality of the precursor iron phosphate. Among them, the iron-phosphorus molar ratio of the iron phosphate raw material is an important factor affecting the quality of lithium iron phosphate products synthesized by the solid phase process. In order to ensure the performance of lithium iron phosphate products, some manufacturers have high requirements on the iron-phosphorus molar ratio range of the iron phosphate raw materials used in the synthesis, and some manufacturers even narrow the iron-phosphorus molar ratio range of the iron phosphate raw materials to 0.96-0.97. The above shortcomings have caused an increase in production costs, which has restricted the promotion and application of this process route under the background of overcapacity and fierce market competition.

[0004] In the prior art, much attention is paid to the preparation process of lithium iron phosphate and its related parameters, but no attention is paid to the problem that the iron-phosphorus molar ratio in the iron phosphate raw material leads to excessively high raw material prices and increased production costs. Although CN 201810218159.9 discloses that the iron-phosphorus molar ratio in the raw material is controlled to be 0.95-0.98:1 to improve the crystallization performance of lithium iron phosphate, promote primary particle growth, increase the material tap density, and avoid the generation of impurities, the iron-phosphorus molar ratio range is still small, and it is still not suitable for iron phosphate raw materials with low phosphorus content and high iron content. Moreover, the button battery made of lithium iron phosphate obtained by this method has a charge capacity of 141mAh / g and a discharge capacity of 140mAh / g at a rate of 1C, and the electrical performance needs to be strengthened.

[0005] Another example is the method disclosed in CN 201811315617.7. The raw material used is ferric phosphate dihydrate, and its iron-phosphorus molar ratio is 0.99 to 1.0:1, which is still a small range. In addition, the method is to obtain metal oxides uniformly doped with battery-grade iron phosphate after ball milling, drying, and calcining of the raw material. After treatment, the iron-phosphorus molar ratio in the obtained iron phosphate changes, and the specific iron-phosphorus molar ratio in the obtained iron phosphate is not disclosed. This method cannot expand the iron-phosphorus molar ratio range of raw materials used in lithium iron phosphate production to effectively reduce the price of the raw materials used.

[0006] In order to solve the above problems, a method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratio is needed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios. The molar ratio of iron to phosphorus in the iron phosphate used in the method can reach 0.960 to 1.02:1, which effectively expands the molar ratio range of iron to phosphorus in the iron phosphate raw material, effectively reduces the price of raw materials used in production, and the method has a simple process and is suitable for use in large-scale industrial production.

[0008] The scheme of the present invention is:

[0009] A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios comprises the following steps:

[0010] 1) After mixing a carbon source, iron phosphate and a lithium source, a phosphorus supplement is added according to 0.2-1.2% of the mass of the iron phosphate, and water is added to prepare slurry to obtain slurry a; the molar ratio of iron to phosphorus in the iron phosphate is 0.960-1.02:1; the molar ratio of the iron phosphate to the lithium source is 1:1.00-1.05; the amount of the carbon source added accounts for 5-10% of the total mass of the iron phosphate and the lithium source;

[0011] 2) The slurry a is stirred, ball-milled, spray-dried, calcined, and air-flow-pulverized to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 2.0 μm.

[0012] As a preferred technical solution, the molar ratio of iron to phosphorus in the iron phosphate in step 1) is 0.981-0.989:1, and the purity of lithium iron phosphate obtained by using the iron phosphate raw material with this element ratio meets production needs. After the obtained product is made into a battery, various electrical properties are excellent.

[0013] As a preferred technical solution, the molar ratio of iron to phosphorus in the iron phosphate in step 1) is 1.01-1.02:1. The purity of lithium iron phosphate obtained by using the iron phosphate raw material with this element ratio meets production needs, and the obtained product has excellent electrical properties after being made into a battery.

[0014] As a preferred technical solution, in the step 1), when the slurry a is prepared, the phosphorus supplement used is one or more of phosphoric acid, monoammonium phosphate and lithium dihydrogen phosphate, and water is added as a dispersant; the solid content of the obtained slurry a is 30-40%;

[0015] As a preferred technical solution, the lithium source in step 1) is one or more of lithium hydroxide, lithium carbonate, lithium oxalate, lithium acetate, lithium nitrate, lithium phosphate and lithium dihydrogen phosphate;

[0016] The carbon source is one or more of glucose, sucrose, citric acid, maltose, cyclodextrin, fructose and polyethylene glycol.

[0017] As a preferred technical solution, in the step 2), the particle size of the medium used for ball milling the slurry a is 0.2-0.5 mm; the medium is zirconium balls; and when the particle size of the material after ball milling is 0.35-0.40 μm, a mixed slurry b is obtained.

[0018] As a preferred technical solution, the ball milling operation of slurry a in step 2) is: first use zirconium balls with a particle size of 0.5 mm for 1 hour, and then use zirconium balls with a particle size of 0.2 mm for 0.5 hour, and the rotation speed during the ball milling process is 1500 r / min.

[0019] As a preferred technical solution, the spray drying parameters in the step 2) are as follows: the spray drying inlet temperature is 220-240°C; the outlet temperature is 90-110°C; the spray drying nozzle speed is 250-300Hz; and after spray drying, a carbon-coated spherical lithium iron phosphate precursor powder is obtained.

[0020] As a preferred technical solution, the calcination conditions in the step 2) are calcination under the protection of inert gas at a temperature of 750-800° C. for 6-8 hours.

[0021] As a preferred technical solution, the stirring in step 2) is mechanical stirring for 30 minutes.

[0022] Advantages of the present invention:

[0023] 1) The method for preparing high-density lithium iron phosphate based on wide-range iron-phosphorus ratio iron phosphate provided by the present invention is applicable to iron phosphate raw materials with an iron-phosphorus molar ratio of 0.960 to 1.020. While significantly reducing the cost of using iron phosphate raw materials, it ensures that the various properties of the obtained lithium iron phosphate meet the requirements. The process is simple and energy-efficient, has high energy utilization efficiency, and can be quickly industrialized. The method adds a phosphorus supplement of 0.2 to 1.2% by mass of iron phosphate, which can form a PO4 tetrahedral structure during the sintering growth process, and participate in the carbon reduction of Fe 3+ , and then melted and crystallized again to form lithium iron phosphate. After the synthesized lithium iron phosphate material is made into a battery, it has a higher 0.1C discharge specific capacity and powder compaction density.

[0024] 2) The method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratio provided by the present invention provides phosphorus elements in the synthesis process of lithium iron phosphate by regulating the phosphorus supplementation auxiliary agent, balances the element differences in the lithium iron phosphate generation process, and generates lithium iron phosphate products with stable iron-phosphorus molar ratio, high discharge performance, and high compaction density. After the obtained lithium iron phosphate product is made into a battery, the 0.1C charge can reach 160.34mAh / g; the 0.1C discharge can reach 159.12mAh / g; the first efficiency can reach 99.35%; the compaction density can reach 2.556g / cm 3 , the battery performance is better. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention provides a SEM image of the lithium iron phosphate in Example 2; wherein a) is 9.4 mm*10 k; b) is 10.2 mm*10 k;

[0026] Figure 2 The present invention provides an XRD diagram of the lithium iron phosphate in Example 2;

[0027] Figure 3 The present invention provides the electrochemical performance diagram of lithium iron phosphate in Example 2, wherein a) is a 0.1C charge and discharge curve; b) is a rate charge and discharge curve. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0029] Unless otherwise specified, the materials and instruments used in the following examples were obtained from commercial channels; the detection methods used were all existing methods unless otherwise specified.

[0030] The iron phosphate used in the following examples, which has an iron-phosphorus molar ratio not in the range of 0.96 to 0.97, is a defective product and has a selling price lower than that of the iron phosphate in the range of 0.96 to 0.97, which is about RMB 7,000 to 8,000 per ton.

[0031] Embodiment 1:

[0032] Take 500g of iron phosphate with an iron-phosphorus molar ratio of 1.00-1.02, add lithium carbonate at a molar ratio of 1:1.00-1.05 between iron phosphate and lithium; add glucose at 5-10% of the total mass of iron phosphate and lithium carbonate; add phosphorus supplement at 1.2% of the mass of iron phosphate, add water as a dispersant to prepare a slurry a with a solid content of 40%, and stir for 30 minutes with a mechanical stirrer for use. Since the iron phosphate raw material used is purchased in tons, the iron-phosphorus molar ratio range is relatively wide, and the single batch production volume is 0.5 tons, so the iron-phosphorus molar ratio is a range value.

[0033] The slurry a was put into a sand mill and ground with 0.5 mm and 0.2 mm zirconium balls for 1 h and 0.5 h, respectively, at a rotation speed of 1500 r / min, so that the material particle size reached 0.35-0.40 μm to obtain a mixed slurry b.

[0034] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0035] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0036] The lithium iron phosphate material is subjected to air flow pulverization to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 1.2 μm.

[0037] Embodiment 2:

[0038] Take 500g of iron phosphate with an iron-phosphorus molar ratio of 0.985-1.00, iron phosphate and lithium carbonate according to a molar ratio of 1:1.00-1.05; glucose according to 5-10% of the total mass of iron phosphate and lithium carbonate; phosphorus supplement according to 0.8% of the mass of iron phosphate, add water as a dispersant to prepare a slurry a with a solid content of 40%, use a mechanical stirrer to stir for 30 minutes and then set aside. Since the iron phosphate raw material used is purchased in tons, the iron-phosphorus molar ratio range is relatively wide, and the single batch production volume is 0.5 tons, so the iron-phosphorus molar ratio is a range value.

[0039] The slurry a was put into a sand mill and ground with 0.5 mm and 0.2 mm zirconium balls for 1 h and 0.5 h, respectively, at a rotation speed of 1500 r / min, so that the material particle size reached 0.35-0.40 μm to obtain a mixed slurry b.

[0040] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0041] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0042] The lithium iron phosphate material is subjected to air flow pulverization to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 1.2 μm.

[0043] Embodiment 3:

[0044] 500g of iron phosphate with an iron-phosphorus molar ratio of 0.970-0.985, iron phosphate and lithium carbonate at a molar ratio of 1:1.00-1.05; glucose at 5-10% of the total mass of iron phosphate and lithium carbonate; phosphorus supplement at 0.5% of the mass of iron phosphate, water as a dispersant is added to prepare a slurry a with a solid content of 40%, and stirred for 30 minutes with a mechanical stirrer for use. Since the iron phosphate raw material used is purchased in tons, the iron-phosphorus molar ratio range is relatively wide, and the single batch production volume is 0.5 tons, so the iron-phosphorus molar ratio is a range value.

[0045] The slurry a was put into a sand mill and ground with 0.5 mm and 0.2 mm zirconium balls for 1 h and 0.5 h, respectively, at a rotation speed of 1500 r / min, so that the material particle size reached 0.35-0.40 μm to obtain a mixed slurry b.

[0046] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0047] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0048] The lithium iron phosphate material is subjected to air flow pulverization to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 1.2 μm.

[0049] Embodiment 4:

[0050] 500g of iron phosphate with an iron-phosphorus molar ratio of 0.960-0.970, iron phosphate and lithium carbonate at a molar ratio of 1:1.00-1.05; glucose at 5-10% of the total mass of iron phosphate and lithium carbonate; phosphorus supplement at 0.2% of the mass of iron phosphate, water as a dispersant is added to prepare a slurry a with a solid content of 40%, and a mechanical stirrer is used to stir for 30 minutes for use. Since the iron phosphate raw material used is purchased in tons, the iron-phosphorus molar ratio range is relatively wide, and the single batch production volume is 0.5 tons, so the iron-phosphorus molar ratio is a range value.

[0051] The slurry a was put into a sand mill and ground with 0.5 mm and 0.2 mm zirconium balls for 1 h and 0.5 h, respectively, at a rotation speed of 1500 r / min, so that the material particle size reached 0.35-0.40 μm to obtain a mixed slurry b.

[0052] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0053] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0054] The lithium iron phosphate material is subjected to air flow pulverization to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 1.2 μm.

[0055] Embodiment 5:

[0056] 1000 kg of iron phosphate with an iron-phosphorus molar ratio of 0.985-1.00 and lithium carbonate at a ratio of 1:1.00-1.05 are added; glucose accounts for 5-10% of the total mass of iron phosphate and lithium carbonate; phosphoric acid accounts for 0.8% of the mass of iron phosphate, and water is added as a dispersant to prepare a slurry a with a solid content of 40%, which is then added to the production line.

[0057] Since the iron phosphate raw materials used are purchased in tons, the iron-phosphorus molar ratio has a wide range and the single batch production volume is 0.5 tons, the iron-phosphorus molar ratio is a range value.

[0058] The slurry a was put into a ton-class production line sand mill, and was coarsely ground and finely ground for 1 hour each, with the rotation speeds of 1100 rpm and 800 rpm, so that the particle size of the material reached 0.35-0.40 μm, to obtain a mixed slurry b;

[0059] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0060] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0061] The lithium iron phosphate material is subjected to air flow pulverization to obtain a lithium iron phosphate product with a D50 of 0.8 to 1.2 μm.

[0062] Comparative Example 1:

[0063] The iron phosphate and lithium carbonate with an iron-phosphorus molar ratio of 1.00 to 1.02 are prepared in a ratio of 1:1.00 to 1.05; glucose is 5 to 10% of the total mass of the iron phosphate and lithium carbonate; phosphorus supplement is 0.1% of the mass of the iron phosphate, and water is added as a dispersant to prepare a slurry a with a solid content of 40%, which is stirred for 30 minutes with a mechanical stirrer for use. Since the iron phosphate raw material used is purchased in tons, the iron-phosphorus molar ratio range is relatively wide, and the single batch production volume is 0.5 tons, so the iron-phosphorus molar ratio is a range value.

[0064] The slurry a was put into a sand mill and sand-milled for 1 h and 0.5 h using 0.5 mm and 0.2 mm zirconium balls respectively at a rotation speed of 1500 r / min to make the particle size of the material reach 0.35-0.40 μm to obtain a mixed slurry b.

[0065] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0066] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0067] The lithium iron phosphate material is subjected to air flow pulverization to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 1.2 μm.

[0068] Comparative Example 2:

[0069] The iron phosphate and lithium carbonate with an iron-phosphorus molar ratio of 0.985 to 1.00 are prepared in a ratio of 1:1.00 to 1.05; the glucose is 5 to 10% of the total mass of the iron phosphate and lithium carbonate; the phosphorus supplement is 1.5% of the mass of the iron phosphate, and water is added as a dispersant to prepare a slurry a with a solid content of 40%, which is stirred for 30 minutes with a mechanical stirrer for use. Since the iron phosphate raw material used is purchased in tons, the iron-phosphorus molar ratio range is relatively wide, and the single batch production volume is 0.5 tons, so the iron-phosphorus molar ratio is a range value.

[0070] The slurry a was put into a sand mill and sand-milled for 1 h and 0.5 h using 0.5 mm and 0.2 mm zirconium balls respectively at a rotation speed of 1500 r / min to make the particle size of the material reach 0.35-0.40 μm to obtain a mixed slurry b.

[0071] The slurry b was spray dried, the spray drying inlet temperature was 230° C., the outlet temperature was set to 105° C., and the spray drying nozzle speed was 280 Hz to obtain spherical lithium iron phosphate carbon-coated precursor powder.

[0072] Under the protection of inert gas, the precursor powder was calcined in a box furnace at 780°C for 8 hours to obtain the lithium iron phosphate positive electrode material.

[0073] The lithium iron phosphate material is subjected to air flow pulverization to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 1.2 μm.

[0074] Comparative Example 3:

[0075] The difference from Examples 1 to 2 is that the iron-phosphorus molar ratio of the iron phosphate used is 0.96 to 0.97:1, the raw material cost of the method is 10,000 yuan / ton, and after using 5 tons of raw materials, the production cost of the iron phosphate is 50,000 yuan.

[0076] It can be seen from Comparative Example 3 that the method provided by the present invention can reduce the production cost by 20-30% by adopting iron phosphate with a wider iron-phosphorus molar ratio range, which can effectively reduce the production cost.

[0077] The physical and chemical properties, electrochemical properties and compaction density of the lithium iron phosphate products obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were tested respectively, and the results are listed in Table 1.

[0078] 1. Electrochemical test method and parameter description:

[0079] The lithium iron phosphate product of the sample to be tested is mixed with the conductive agent SP and the binder PVDF in a mass ratio of 90:6:4 to prepare a slurry, and the obtained slurry is coated on the aluminum foil current collector, dried, rolled, and sliced ​​to obtain electrode discs, which are then weighed and vacuum-baked in an oven at 120°C for 5 hours for use;

[0080] 2. Preparation of the battery to be tested: lithium metal is used as the negative electrode, Celgard2320 lithium battery diaphragm is used as the diaphragm, 2032 button battery shell is assembled as the button battery, and the electrode disc obtained above is used as the positive electrode; the obtained battery is subjected to rate performance test on the blue electric performance test system.

[0081] 3. Physical and chemical performance testing methods:

[0082] 3.1 Determination of iron content

[0083] Weigh 4g of the sieved sample, add 25mL of hydrochloric acid, and heat at low temperature to dissolve. After cooling, transfer to a 250mL volumetric flask and make up the volume, shake well. Add hydrochloric acid and heat. While hot, shake the conical flask and add the stannous chloride solution drop by drop until the color of the solution changes from brown to light yellow. Add 4 to 5 drops of sodium tungstate indicator solution, and add titanium trichloride solution drop by drop while shaking the conical flask until the solution is light blue. Add 50mL of water and titrate with potassium dichromate standard titration solution until the blue color just fades. Dilute to 100mL with water, add 10mL of sulfuric acid-phosphoric acid mixed solution, 3 to 4 drops of sodium diphenylamine sulfonate indicator solution, and titrate with potassium dichromate standard titration solution until a stable purple-red color (does not disappear in 30s) is the end point.

[0084] 3.2 Determination of phosphorus content

[0085] Use a pipette to transfer 25mL of test solution A to a 250mL volumetric flask. Transfer 10mL of this test solution, add 10mL of nitric acid solution, and add water to about 100mL. Slowly heat to boil and keep it at a slight boil for 5min. Add 50mL of quinoline molybdate solution and keep warm for 30s. Use a glass crucible to filter the supernatant liquid and wash the precipitate. Place the glass crucible and the precipitate in an electric constant temperature drying oven at 180℃±5℃ and dry for 45min. Take it out, cool it slightly, place it in a desiccator, and cool it to room temperature. Weigh it to an accuracy of 0.0002g.

[0086] 3.3 Iron to phosphorus molar ratio (Fe / P)

[0087] The iron-phosphorus molar ratio is the ratio of the molar number of iron to the molar number of phosphorus, Ms, calculated according to formula (1):

[0088] Ms=W1 / W2x0.5545 (1)

[0089] Where:

[0090] W1 is equal to the measured mass fraction of iron (Fe);

[0091] W2 is equal to the measured mass fraction of phosphorus (P);

[0092] 0.5545 – The ratio of the relative molecular mass of phosphorus to the relative molecular mass of iron.

[0093] 4. Compaction density detection method:

[0094] Clean the inside of the clamp and the gasket with alcohol, match the clamp with the base, put the lower gasket into the clamp (do not press it down when putting it in, it is normal to fall naturally), weigh the sample on a precision electronic scale for 1g, pour the sample into the clamp, put the upper gasket into the clamp, do not press it down when putting it in, it is normal to fall naturally, put in the plunger, let the plunger fall naturally, put the film pressing fixture on the equipment pressure plate, and start the test (before the test, do blank value compression to clear deformation). The test pressure is 1.0T, 2.0T, 3.0T. Press the run command button, and the equipment will test according to the test plan set by the software.

[0095] 5. The lithium iron phosphate product obtained in Example 2 was subjected to SEM testing, and the results obtained were as follows: Figure 1 As shown in the figure, the lithium iron phosphate product particles obtained by the method provided by the present invention are full and have a regular spherical structure; the lithium iron phosphate product in Example 2 is subjected to XRD detection, and the results obtained are as follows Figure 2 As shown in the figure, it can be seen that the obtained lithium iron phosphate product has a high purity and a crystallinity of 86.1%, which is sufficient to meet the market demand for lithium iron phosphate; Figure 3The present invention provides the electrochemical performance result diagram of lithium iron phosphate in Example 2, wherein a) 0.1C charge-discharge curve; b) rate charge-discharge curve. The charge-discharge performance result values ​​of each embodiment and comparative example sample are listed in Table 1.

[0096] Table 1. Performance data of lithium iron phosphate products obtained in various embodiments and comparative examples

[0097]

[0098] As can be seen from Table 1, increasing the amount of phosphorus supplementing agent added (Comparative Example 2) or reducing the amount of phosphorus supplementing agent added (Comparative Example 1) cannot improve the 0.1C charge and discharge performance of the obtained battery, and the amount of phosphorus supplementing agent added outside the range provided by the present invention will affect the subsequent performance of the battery. Comparing Example 4 with Comparative Example 3, adding a small amount of phosphorus supplementing agent can still supplement the phosphorus source, improve the discharge performance and compaction density, and the compaction density of the lithium iron phosphate material obtained in Comparative Examples 1-2 is also low, indicating that the range of the amount of phosphorus supplementing agent added is directly related to the various properties of the obtained lithium iron phosphate material.

[0099] As can be seen from the above table, the lithium iron phosphate precursor provided by the method of the present invention can meet the element ratio balance during the sintering growth process, form a more stable PO4 tetrahedral structure, and participate in the carbon reduction of Fe 3+ The crystal structure is not easy to collapse, and re-melts and crystallizes to form lithium iron phosphate. After the battery is made of the material by the method shown in Examples 1 to 5, it has a higher 0.1C discharge specific capacity.

[0100] However, even if a phosphorus supplement is added to the lithium iron phosphate obtained in Comparative Examples 1 to 2, the problem of excessively high iron content in the obtained lithium iron phosphate cannot be improved. Moreover, the lithium iron phosphate obtained in Comparative Examples 1 to 2 has many crystal defects. During the reaction of lithium carbonate and iron phosphate, lithium ions are difficult to embed into the iron phosphate structure. The lithium content in the obtained lithium iron phosphate product is low and insufficient, resulting in a low discharge capacity of the battery made using the material, which cannot meet the corresponding performance indicators.

[0101] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios, characterized in that: The following steps are involved: 1) After mixing a carbon source, iron phosphate and a lithium source, a phosphorus supplement is added according to 0.2-1.2% of the mass of the iron phosphate, and water is added to prepare slurry to obtain slurry a; the molar ratio of iron to phosphorus in the iron phosphate is 0.960-1.02:1; the molar ratio of the iron phosphate to the lithium source is 1:1.00-1.05; the amount of the carbon source added accounts for 5-10% of the total mass of the iron phosphate and the lithium source; 2) The slurry a is stirred, ball-milled, spray-dried, calcined, and air-flow-pulverized to obtain D 50 Lithium iron phosphate products in the range of 0.8 to 2.0 μm.

2. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: In the step 1), the molar ratio of iron to phosphorus in the ferric phosphate is 0.981 to 0.989:

1.

3. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: In the step 1), the molar ratio of iron to phosphorus in the ferric phosphate is 1.01-1.02:

1.

4. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: When the slurry a is prepared in step 1), the phosphorus supplement agent used is one or more of phosphoric acid, monoammonium phosphate and lithium dihydrogen phosphate, and water is added as a dispersant; the solid content of the obtained slurry a is 30-40%.

5. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: 1) The lithium source is one or more of lithium hydroxide, lithium carbonate, lithium oxalate, lithium acetate, lithium nitrate, lithium phosphate and lithium dihydrogen phosphate; The carbon source is one or more of glucose, sucrose, citric acid, maltose, cyclodextrin, fructose and polyethylene glycol.

6. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: In the step 2), the particle size of the medium used for ball milling the slurry a is 0.2-0.5 mm; the medium is a zirconium ball; and when the material particle size is ball milled to 0.35-0.40 μm, a mixed slurry b is obtained.

7. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1 or 6, characterized in that: The ball milling operation of slurry a in step 2) is as follows: firstly, milling with zirconium balls with a particle size of 0.5 mm for 1 hour, and then milling with zirconium balls with a particle size of 0.2 mm for 0.5 hour, and the rotation speed during the ball milling process is 1500 r / min.

8. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: The spray drying parameters in the step 2) are as follows: the spray drying inlet temperature is 220-240° C.; the outlet temperature is 90-110° C.; the spray drying nozzle speed is 250-300 Hz; and after spray drying, a carbon-coated spherical lithium iron phosphate precursor powder is obtained.

9. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: The calcination conditions in the step 2) are calcination under the protection of inert gas at a temperature of 750-800° C. for 6-8 hours.

10. A method for preparing high-density lithium iron phosphate based on iron phosphate with a wide range of iron-phosphorus ratios as claimed in claim 1, characterized in that: The stirring in step 2) is mechanical stirring for 30 minutes.

Citation Information

Patent Citations

  • Method for preparing metal oxide uniformly doped battery grade iron phosphate

    CN109713299A

  • Lithium iron phosphate positive electrode material and preparation method

    CN110277542A